G542(P) What really matters? Standards of care in children and young people's healthcare. (25th October 2020) - Hannah, R; Conn, R; Hargreaves, D; Wortley, E; Ruzangi, J; Sparrow, E; Davison, G
Abstract : Background: Measuring the quality of children and young people's (CYP's) healthcare services is an essential process for quality assurance, quality improvement and accountability, so that better care can be provided. Past quality measures created without CYP's input may have been missing 'what matters' to CYP themselves. Aims: To explore key features of healthcare quality measures most highly regarded by CYP's and consider factors influencing their priorities; To compare findings with parents and healthcare professionals (HCPs) perceptions of quality measures. Method: This qualitative study was undertaken as part of a Modified Delphi consensus study. CYP's, parents' and HCPs' views on 32 widely-used determinates for CYP's healthcare quality were captured during 3 separate focus group discussions. Measures were classified within General Practice, acute care and long-term care needs. Participants discussed the quality measure statements on which they had voted on during the day. Transcripts were coded by thematic analysis using NVivo12 software. Results: Participants included 12 CYP, 6 parents and 12 HCPs from a range of healthcare agencies. CYP value measures that reflect co-production and partnership in decision-making. They desire flexibility and choice regarding their health needs (i.e. ownership of healthcare records and an individualised approach to transition). Measures such as the four-hour A&E wait and annual weight measurements are considered arbitrary. CYP value seamless communication between services and offer digitalization of healthcare as a solution. Ideal measures should reflect a whole systems response with an identifiable patient outcome. In contrast, parents value accessibility and convenience, whereas HCPs value family-centred care practices, timely communication and access to specialist services. CYPs and parents' priorities are informed by personal or family experience of illness, whereas professionals opinions reflect wider system structures. All groups agreed that understanding and responding to emotional health was of vital importance. CYP want non-judgemental, trusting relationships with HCP enabling open discussion about psychosocial health and wellbeing. Discussion: CYP offer a unique alternative perspective on the meaning of quality within quality measures. Service evaluation and improvement led by user-informed service measures will create a healthcare system which truly works with and for CYP in synchrony.